2002
DOI: 10.1001/jama.288.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, Universal Screening for Acute HIV Infection in a Routine HIV Counseling and Testing Population

Abstract: These findings suggest the widespread diagnosis of acute HIV infections in a routine testing population is not only possible but feasible using specimen pooling and nucleic acid testing. These additional procedures may increase diagnostic yield by approximately 10% compared with conventional HIV antibody testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
119
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(122 citation statements)
references
References 17 publications
3
119
0
Order By: Relevance
“…After consent is obtained, a blood sample is drawn and sent to the state laboratory for antibody testing, as well as acute HIV screening. 33 HIV test results are provided in person approximately 2 weeks after the pretest counseling session. During the data collection period, there were two HIV test counselors at the local health department, both of similar demographics (Caucasian females, mid 30s).…”
Section: Settingmentioning
confidence: 99%
“…After consent is obtained, a blood sample is drawn and sent to the state laboratory for antibody testing, as well as acute HIV screening. 33 HIV test results are provided in person approximately 2 weeks after the pretest counseling session. During the data collection period, there were two HIV test counselors at the local health department, both of similar demographics (Caucasian females, mid 30s).…”
Section: Settingmentioning
confidence: 99%
“…14, S2). Pooling strategies for HIV detection in clinical testing have recently been piloted in Swiss (15), Indian (16), and US (14) clinical-HIV-testing populations. The results suggest that HIV RNA testing -if based on pooling of antibody-negative specimens -can efficiently identify acute HIV infections in clinical testing.…”
mentioning
confidence: 99%
“…Especially in clinicaltesting populations expected to contain low numbers of acute, antibody-negative infections, pooling affords remarkable increases in cost efficiency and predictive value. Clinical studies have clearly indicated that voluntary counseling and testing (VCT) enhanced to incorporate HIV RNA screening can be both clinically (14) and economically feasible (14,16).…”
mentioning
confidence: 99%
“…Pooled plasma has been shown to allow for the identification of patients in the acute phase of disease [6][7][8] . Since individual HIV RNA testing is expensive, a preliminary test of a mixture of plasma (pool) from different individuals could be performed.…”
Section: Patients With Incident Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%